Investigation on culture and health status of Mrigal Cirrhinus cirrhosus from the farming system of Mymensingh region - Ahmed, GU; Konica, K; Ali, MF; Khatun, T (Journal of the Bangladesh Agricultural University, 2014)
Indian major carp, Cirrhinus cirrhosus was considered to monitor culture and health status in farm condition from Bhaluka and Muktagacha of Mymensingh region of Bangladesh for a period of seven months starting from September, 2010 to March, 2011. Monthly sampling was carried out for growth and health condition. Samples of skin and muscle, gill, liver and kidney were observed by clinical and histological techniques. Water temperature was at unfavorable levels but, dissolved oxygen, pH, alkalinity, ammonia and nitrite of water were within the favorable range for fish culture during the months of December and January. Clinically weak body, rough skin, scale loss, thick gill filaments, ulcer and gray brownish color were observed. Among the affected fish organs like skin, muscle and gill were found to be more affected than those of the internal organs, liver and kidney. Major pathologies in the skin and muscle were loss of epidermis and dermis, presence of fungal granuloma, fungal hyphae, necrosis, hemorrhages, vacuums and melanocytes. Protozoan cysts, clubbing, hemorrhages, necrosis and hypertrophy were found in the gill. Necrosis, hemorrhage, pyknosis and vacuums were observed in liver. Common pathological signs like necrosis, hemorrhage, pyknosis, vacuums and degenerated kidney tubules were noticed in kidney. Overall, in the clinical and histopathological studies fishes were found to be more affected during the colder months i.e., December and January. Whereas, in the month of February the pathological condition of fish gradually started to heal up. In histopathological observation, fishes of Bhaluka farms were more affected than that of Muktagacha fish farms. Epizootic ulcerative syndrome (EUS) and protozoan diseases were noticed in Bhaluka fish farms. DOI: http://dx.doi.org/10.3329/jbau.v11i2.19947 J. Bangladesh Agril. Univ. 11(2): 391-397, 2013